Contract Design by Service Providers with Private Effort - Zhang, Hao; Kong, Guangwen; Rajagopalan, Sampath (Management Science, 2018)
We investigate the performance of two commonly used pricing schemes—hourly-rate contract and two-part tariff—in service environments where the buyer’s valuation is invisible to the service provider and the provider’s effort may not be visible to the buyer. In the private effort environment, we further distinguish between situations where the contract may be based on the outcome or on the effort reported by the provider. We show that under the two-part tariff, when effort is private, the provider can achieve the same profit as under public effort by contracting on reported effort and will be worse off by contracting on outcome. Under the hourly-rate contract, compared with the public effort case, the provider may be better or worse off in keeping effort private and contracting on the reported effort, and the trade-off is affected by the degree of outcome uncertainty in a nontrivial way. We find that a provider’s profits under an hourly-rate contract are as good as under a two-part tariff over a sizable parameter regime when contracting on reported effort. The online appendix is available at https://doi.org/10.1287/mnsc.2017.2743 . This paper was accepted by Vishal Gaur, operations management.